A Roadmap for Aspiring Surgeon-Scientists in Today's Healthcare Environment. Issue 1 (January 2019) - Goldstein, Allan M.; Blair, Alex B.; Keswani, Sundeep G.; Gosain, Ankush; Morowitz, Michael; Kuo, John S.; Levine, Matthew; Ahuja, Nita; Hackam, David J.
Abstract : Objective: Surgeon-scientists are an essential component of the field of academic surgery, contributing to the fundamental understanding of disease and the discovery of innovative therapies. Despite this recognized value, the current landscape of academic medicine presents significant barriers to establishing and maintaining a successful career as a surgeon performing basic/translational research. Our objective is to define these barriers to academic success for surgeons, and to provide a consensus strategy for optimizing the chances of success. Summary Background Data: There is a significant decline in the proportion of academic surgeons who are pursuing basic science/translational research, which represents a potential threat to the very identify of the translational surgeon-scientist. Methods: Based on published literature and expert opinion, the Basic Science Committee of the Society of University of Surgeons prepared this roadmap to encourage and guide the next generation of surgeon-scientists as they embark on their academic careers. Results: This roadmap highlights key elements to consider in choosing an initial job and the importance of identifying a team of committed mentors. Expectations and guidelines for the first several years in practice are offered. Conclusions: With guidance and mentorship, aspiring surgeonscientists can overcome the challenges inherent in choosing this career path and sustain the important legacy of those before them.